Interferon regulatory factor 8 governs myeloid cell development - Xia, Xueli; Wang, Wenxin; Yin, Kai; Wang, Shengjun (Cytokine & growth factor reviews, 2020)
[Display omitted] •IRF8 is composed of the N-terminal region which is a helix-turn-helix DNA binding domain, and C-terminal IRF association domain.•IRF8 controls the lineage specification of dendritic cells and monocyte/macrophage development.•IRF8 is a negative regulator of MDSCs and involved in neoplasia deterioration.•Using or developing specific targeted therapies for IRF8 may contribute to the treatment and prognosis of immune disorders. Interferon regulatory factors (IRFs) are a family of central transcriptional regulators that produce type I interferon and regulate innate and adaptive immune responses. Interferon regulatory factor 8 (IRF8) exists mainly in hematopoietic cells and is essential for the development of several myeloid lineages, including monocytes/macrophages and dendritic cells. In recent years, an increasing number of studies have focused on the roles of IRF8 in the differentiation of myeloid pedigree and MDSC aggregation in diseases such as tumors. In this review, we provide a comprehensive overview of the roles of IRF8 in the regulation of myeloid cell development, with particular reference to multiple disease conditions. Clarifying the various functions of IRF8 may suggest targets for therapeutic interventions.